Studying clone evolution using incremental clone detection. Issue 2 (3rd September 2010) - Göde, Nils; Koschke, Rainer; Ferenc, Rudolf; Knodel, Jens; Winter, Andreas
SUMMARY Finding, understanding and managing software clones—passages of duplicated source code—is of large interest in research and practice. Analyzing the evolution of clones across multiple versions of a program adds value to both applications. Although there is an abundance of techniques to detect clones, current approaches are limited to a single version of a program. The current techniques to track clones utilize these single‐version approaches and map clones of consecutive versions retroactively. This causes an unnecessary overhead in runtime and may lead to an incorrect mapping due to ambiguity. In this paper, we present an incremental clone detection algorithm, which detects clones based on the results of the previous version's analysis. It creates a mapping between clones of consecutive versions along with the detection. We evaluated our incremental approach regarding its advantage in runtime as well as the usefulness of the mapping for studies on the clone evolution. Copyright © 2010 John Wiley & Sons, Ltd.